(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2020)
Background: - Physicians are confronted on having ECG in patients with acute stroke as it can mimic that of myocardial infarction or ischaemia. Repolarization and ischemic-like electrocardiographic (ECG) changes observed during acute phase of stroke may cause diagnostic and management dilemmas for the physicians. Aim:- The aim and objective of this study to identify the prevalence of ECG changes in acute stroke patients admitted to medicine units of Dhaka Medical College Hospital. Materials and Method: - This 6-month period observational study was carried out among 100 of acute stroke patients admitted in different medicine wards of Dhaka Medical College Hospital (DMCH). ECG was done in all patients after their admission to hospital within 48 hours of developing their symptoms. Association of various types of ECG changes were identified and observed. Results: - Among 100 patients,55% had ischaemic stroke and 45% had haemorrhagic stroke. 43.63% aged between 61-70 years had ischaemic stroke and 28.28% aged between 61-80 years had haemorrhagic stroke. Female had higher frequency of ischaemic stroke 52.72% and male had higher frequency of haemorrhagic stroke 75.56%. Abnormal ECG found 84.44% in haemorrhagic stroke and 54.54% in ischaemic stroke. Of all abnormal ECG, ST depression is most frequent and 42.22% in haemorrhagic stroke, T inversion is next 20% in ischaemic stroke, AF is present in 18.18% in ischaemic stroke and QT prolongation is found in 17.77% in hemorrhagic stroke. There considerable variation of ECG changes according to CT scan evidence of particular area of brain involvement like ST depression (28.88%) found in gangliothalamic bleed in haemorrhagic stroke, AF is found (16.36%) in insular area involvement in ischaemic stroke, T inversion is more (12.72%) in large MCA territory infarctive stroke and QT prolongation (11.11%) is found in intracerebral haemorrhage including SAH. Predictable early in hospital mortality is associated with AF 37.5% and with QT prolongation 31.25%. Conclusion:- In haemorrhagic stroke the ECG abnormalities were more frequent then in ischaemic stroke. The most common abnormalities were ST depression, T wave inversion, AF and QT prolongation. AF and QT prolongation has association of early in hospital mortality. J Bangladesh Coll Phys Surg 2020; 38(4): 166-171